A lousa digital e o ensino da língua inglesa na perspectiva de professores - COSTA, Dilermando Moraes (2019)
This study investigates the transformations in the training and teaching actions resulting from the introduction of the interactive whiteboard as pedagogical tool for the teaching of the English language. Such research is justified by the need to understand the implications of integrating information and communication technologies, such as the interactive whiteboard and their software, to the process of teaching and learning the English language, contributing to the interdisciplinary analysis of the connections between language teaching and the training of in-service teachers. The goals of this research include: to identify the type of training that teachers of English received for the use of information and communication technologies and, more specifically, the interactive whiteboard; to describe the possible changes in the didactic-pedagogical approach of English lessons in virtue of the adoption of the interactive whiteboard; and to discuss the constraints regarding the incorporation of interactive whiteboards to the teaching of English. It is a qualitative research, using the snowball sampling technique which aimed to identify in this community of teachers of English those of acknowledged competence in the use of the electronic whiteboard. 10 participants were selected based on their peers suggestion and they took part in semi-structured interviews between the first and second semesters of 2013. We conducted the study and analysis of the data from the reports of the participants, which led to the formulation of explanatory arguments and theoretical construction. As a result of this research, we identified changes in the profile of the teachers of English, as well as new demands for training and professional performance introduced by technological resources.